Komposisi dan Persentase Serangan Penggerek Batang Padi pada Varietas yang Berbeda di Subak Renon, Denpasar Selatan - Wikantara, Pande Nyoman Bagas; Wijaya, I Nyoman; Yuliadhi, Ketut Ayu (Nandur; Vol 3 No 3 (2023), 2023)
Rice stem borer is the most pest often found in rice plantations and is one of the important pests of rice plants in Indonesia. The purpose of this study is to determine species composition of rice stem borer that attacks Ciherang and Pandanwangi varieties and the percentage attack of rice stem borer on both of varieties. The method carried out is purposive sampling and identification of larvae in the laboratory. The study began with the land survey by figure criteria out for planting rice with different varieties in the same subak that found the suitable criteria in Subak Renon. Then, next step install the ajir with diagonal sampling. This study took 100 larvae in 1 variety every week to determine the composition of species that attack rice in Subak Renon. In addition, the sample was observed every week as many as 10 observations. The results of the research on the both varieties found 3 species of rice stem borer were Scirpophaga incertulas , Sesamia inferens , and Chilo suppresalis . The S. incertulas is the dominat pest found in the two varieties. The attack of rice stem borer on the Pandanwangi variety (8.94%) is higher than the Ciherang variety (7.49%).